2017
DOI: 10.3126/jaim.v5i1.17065
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Various Vasodilators Regimen During Radial Corornary Angiogram: A Prospective Randomised Trial

Abstract: Background and Aims: Coronary intervention through radial artery is a preferred over femoral route. Different vasodilators are used to prevent radial artery spasm. Till date there is no study to compare the effects of various vasodilator regimes during radial coronary angiogram in Nepal. We aim to compare the efficacy of different vasodilator in our patients.Methods and Result: This is a single centre, prospective randomized trial between Verapamil, Nitroglycerine (GTN) and cocktail (Verapamil with GTN). All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies demonstrated mixed results using nitrates and CCBs either alone or in combination as a cocktail. [ 11 12 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated mixed results using nitrates and CCBs either alone or in combination as a cocktail. [ 11 12 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%